GENOMICS AND EPIGENOMICS IN MAIZE HYBRID KERNEL - & et al., Elsahookie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The endosperm in cereals supplies nutrients to the developing kernel and seedling, and it is the primary tissue that gene imprinting occurs. Developing maize (Zea mays L.) endosperms were analysed for allelic gene expression in both reciprocal crosses of inbreds B73 and Mo17. A high-throughput transcriptome sequencing in kernels at 0, 3 up to 15 DAP of both reciprocals were performed, and found a gradual increased paternal transcript expression in 3 and 5 DAP kernels. Meanwhile, in 7 DAP endosperm, most of genes tested gave the ratio 2:1 maternal: paternal, suggesting that paternal genes are almost fully activated at 7 DAP. There were 300 PEGs and 499 MEGs identified across endosperm development stages. A 63 genes out of 116, 234 exhibited parent-specific expression were identified at 7, 10 and 15 DAP. Most of paternally expressed genes was at 7 DAP due to deviation of paternal alleles expression at this stage of development. Imprinted genes in terms of relative expression of maternal and paternal alleles differed at least five folds in both crosses. A total of 179 (1.6%) protein coding genes expressed in the endosperm were imprinted, 68 of them showed maternal preferential expression and 111 paternal expression, besides 38 long noncoding RNA were found imprinted and transcribed in either sense or antisense direction from intronic regions of normal protein coding genes or from intergenic regions. Imprinted genes showed clustering around the genome. A total of 21 imprinted genes in the maize hybrid endosperm had differentially methylated regions (DMRs). All DMRs were found to be hypomethylated in maternal alleles and hypermethylated in paternal alleles. These results confirm a complex mechanism controlling endosperm in maize in imprinting, auxin activity, and development regulation. Studying F2 kernels on F1 plants may shed a new light on controlling kernel number weight in unit of area.